INSTRUMENTS FOR IMPLEMENTING SOCIO-ENVIRONMENTAL RIGHTS IN THE MANAGEMENT OF BRAZILIAN COASTAL PARKS - LIMA, NATHALIA; Teles da Silva, Solange (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2023)
The National System of Conservation Units (Law No. 9,985 / 00) was introduced as part of the normative framework that regulates the creation of Specially Protected Territorial Spaces. Here we analyze notably the conservation units, specifically those that do not allow the direct use of natural resources and predict that the traditional populations residing in their limits must be relocated. However, until it is possible to carry out this resettlement, the public power can carry out actions in order to make the permanence of these populations compatible with the purposes of the unit. Our objective was to identify and analyze some solutions adopted by the management bodies of the state and federal integral protection conservation units, which we consider innovative, as they sought to reconcile the protection of intangible cultural heritage with the conservation of natural resources. First, we made a cut in the research object to analyze the “Park” category and we opted the empirical research methodology, with application of the documentary research method of official public documents, namely, the management plans of federal and state parks approved and made available on the website of the Chico Mendes Institute for Biodiversity Conservation (ICMBio) and the State Environment Secretariats (SMA). After this research, we analyzed three coastal marine parks that presented innovative solutions from a socio-environmental and bio cultural point of view, with regard to the protection of natural and cultural heritage (material and immaterial) and the recognition of traditional lands and territories in the management of protected areas.